PREMATURE OVARIAN FAILURE (POF): GENETIC PREDICTORS AND EARLY PREDICTION OF OVARIAN RESERVE DECLINE - Rakhmonova Mohigul Shodikulovna; Tokhirjonova Aziza Tokhirjonovna (Western European Studies, 2026)
Premature ovarian failure (POF), also referred to as primary ovarian insufficiency (POI), is a complex reproductive disorder characterized by the loss of ovarian function before the age of 40 years. The condition is associated with hypoestrogenism, elevated gonadotropin levels, infertility, and long-term metabolic and cardiovascular consequences. Recent advances in reproductive medicine have highlighted the crucial role of genetic factors in the development of POF, as well as the importance of early identification of declining ovarian reserve. Modern diagnostic strategies combine genetic testing, hormonal assessment, and ultrasonographic evaluation to predict ovarian aging at an early stage. This review analyzes genetic predictors of premature ovarian failure, evaluates methods for early detection of reduced ovarian reserve, and summarizes clinical studies assessing diagnostic accuracy and prognostic value of current testing approaches. Early identification of women at risk allows timely reproductive counseling and fertility preservation strategies, significantly improving clinical outcomes
Keywords: testing; preservation strategies; clinical outcomes; counseling and fertility